Bank loan quality and managerial ability in the US: Do crises matter? / B M Hasanul Banna - B M Hasanul , Banna (2017)
The rapid increase of bank failure raises many questions about loan quality and the ability of the managers. Loans comprise a significant proportion of bank assets, and therefore it is important to manage loan quality so as to ensure a bank’s financial health. Higher loan loss provision in a pre-crisis period could signify that bank managers are more prompt in recognising loan losses. Many managers, however, have been unable to anticipate and understand the conditions of the recent 2007-09 financial crisis. Further, it remains unclear whether higher quality loans are attributed to higher ability managers. Hence, this thesis has two objectives. First, it aims to examine the influence of managerial ability on bank loan quality. Second, it aims to estimate the effect of three crises on the nexus between loan quality and managerial ability of banks. The crises studied are the global financial crisis (GFC), the dot-com bubble, and 9/11 terrorist attacks crisis (DB- 9/11). This study uses data envelopment analysis (DEA) and Tobit regression to estimate the managerial ability proxy. This research also employs the fixed effect panel regression and the panel ordered probit regression to address both the objectives. The results show that managerial ability significantly influences a bank’s loan quality. Hence, banks with more talented (higher ability) managers have less probability of loan default. Further, the association between loan quality and managerial ability is significantly affected by the GFC and DB-9/11 crises. The nexus of loan quality and managerial ability is shown to be strengthened during the GFC; however, the nexus was weakened during the DB-9/11 crisis. The research contributes as follows. First, it contributes to both the bad management hypothesis and the task complexity theory by providing empirical evidence of the relationship between bank loan quality and managerial ability. Second, it also provides empirical evidence on the impact of both financial and non-financial crises on loan quality through the channel of managerial ability. Third, it provides an extension of the managerial ability proxy to the banking industry which makes available a measure of managerial ability of US banks to parties both within and outside the industry. Fourth, the managerial ability and loan quality relationship are shown to be useful tools for forecasting and stress testing purposes for policy makers, regulators and bankers. Fifth, it contributes to the understanding of how managerial ability impacts on loan quality during critical crisis periods. The study has limitations in that it employs a limited sample of US commercial banks over the limited time period of 1991 to 2013. Nonetheless, these limitations do not undermine the significance of the research findings. Instead, it provides directions for future research opportunities.